Fractal and multifractional-based predictive optimization model for stroke subtypes' classification. (July 2020) - Karaca, Yeliz; Moonis, Majaz; Baleanu, Dumitru
Abstract : Significance of singularity spectrum in fractal and multifractional analyses in modern neurosciences. Proposing a novel integrated approach with multi-stage methodology for stroke subtypes' classification Identification of self-similar, significant and regular attributes by multifractal approaches. The critical and determining role of WTMM and BC as efficient approaches to identify self-similarity and regularity for stroke subtypes' classification. A new frontier for accurate diagnosis and maintaining patients' life quality by ANN. Abstract: Numerous natural phenomena display repeating self-similar patterns. Fractal is used when a pattern seems to repeat itself. Fractal and multifractal methods have extensive applications in neurosciences in which the prevalence of fractal properties like self-similarity in the brain, equipped with a complex structure, in medical data analysis at various levels of observation is admitted. The methods come to the fore since subtle details are not always detected by physicians, but these are critical particularly in neurological diseases like stroke which may be life-threatening. The aim of this paper is to identify the self-similar, significant and efficient attributes to achieve high classification accuracy rates for stroke subtypes. Accordingly, two approaches were implemented. The first approach is concerned with application of the fractal and multifractal methods on the stroke dataset in order to identify the regular, self-similar, efficient and significant attributes from the dataset, with these steps: a) application of Box-counting dimension generated BC _ stroke dataset b) application of Wavelet transform modulus maxima generated WTMM _ stroke dataset. The second approach involves the application of Feed Forward Back Propagation (FFBP) for stroke subtype classification with these steps: (i) FFBP algorithm was applied on the stroke dataset, BC _ stroke dataset and WTMM _ stroke dataset. (ii) Comparative analyses were performed based on accuracy, sensitivity and specificity for the three datasets. The main contribution is that the study has obtained the identification of self-similar, regular and significant attributes from the stroke subtypes datasets by following multifarious and integrated methodology. The study methodology is based on the singularity spectrum which provides a value concerning how fractal a set of points are in the datasets (BC_stroke dataset and WTMM_stroke dataset). The experimental results reveal the applicability, reliability and accuracy of our proposed integrated method. No earlier work exists in the literature with the relevant stroke datasets and the methods employed. Therefore, the study aims at pointing a new direction in the relevant fields concerning the complex dynamic systems and structures which display multifractional nature.